2008
DOI: 10.1103/physrevb.77.134440
|View full text |Cite
|
Sign up to set email alerts
|

Damping of field-induced chemical potential oscillations in ideal two-band compensated metals

Abstract: The field and temperature dependence of the de Haas-van Alphen oscillation spectrum is studied for an ideal two-dimensional compensated metal. It is shown that the chemical potential oscillations, which are involved in the frequency combinations observed in the case of uncompensated orbits, are strongly damped and can even be suppressed when the effective masses of the electron-and hole-type orbits are the same. When a magnetic breakdown between bands occurs, this damping is even more pronounced and the Lifshi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 25 publications
4
19
0
1
Order By: Relevance
“…The minimal periodicity T E of the spectrum is, in this case and for a given phase , equal to T E =2bp 0 / m e ‫ء‬ , which is twice the periodicity calculated for an isolated system made of one hole and one electron band. 21 The number of solutions inside each interval of width T E is found to be equal to 2͑p 0 + q 0 ͒ ͑this number is conserved when p varies and can be counted exactly for p =0͒. Given a set of solutions E eh ͑q , n , ͒, n =0,¯,2͑p 0 + q 0 ͒ − 1, we introduce a cutoff function c ͑E͒ such as c ͑E͒ = 1 for E larger than a characteristic energy E c and equal to exp͓−c͑E − E c ͒ 2␦ ͔ for E Յ E c , where ␦ is any positive integer greater than 1 ͑we take ␦ = 4 in the simulations which gives a very smooth cutoff function͒, and c a positive parameter determined self-consistently.…”
Section: Modelmentioning
confidence: 97%
See 1 more Smart Citation
“…The minimal periodicity T E of the spectrum is, in this case and for a given phase , equal to T E =2bp 0 / m e ‫ء‬ , which is twice the periodicity calculated for an isolated system made of one hole and one electron band. 21 The number of solutions inside each interval of width T E is found to be equal to 2͑p 0 + q 0 ͒ ͑this number is conserved when p varies and can be counted exactly for p =0͒. Given a set of solutions E eh ͑q , n , ͒, n =0,¯,2͑p 0 + q 0 ͒ − 1, we introduce a cutoff function c ͑E͒ such as c ͑E͒ = 1 for E larger than a characteristic energy E c and equal to exp͓−c͑E − E c ͒ 2␦ ͔ for E Յ E c , where ␦ is any positive integer greater than 1 ͑we take ␦ = 4 in the simulations which gives a very smooth cutoff function͒, and c a positive parameter determined self-consistently.…”
Section: Modelmentioning
confidence: 97%
“…15,16 Contrary to the above-mentioned examples, the Fermi surface of numerous organic metals is composed of compensated electron-and hole-type closed orbits, 17 yielding many frequency combinations as well, as far as Shubnikov-de Haas oscillations are concerned. [18][19][20] In the case of a Fermi surface composed of two compensated orbits coupled to each other through magnetic breakdown but isolated from the other orbits outside the first Brillouin zone, it has been shown that the oscillations of the chemical potential can be strongly damped 21 which could account for the absence of frequency combinations reported in the de Haas-van Alphen ͑dHvA͒ spectra of two-dimensional ͑2D͒ networks of compensated orbits in fields up to 28 T. 20 However, the Fermi surface considered in Ref. 21 which, to our knowledge, has no counterpart among the compounds synthesized up to now, does not provide a network of orbits and, therefore, do not yield Landau bands in magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have studied the de Haas van Alphen (dHvA) oscillation 15 in the tight-binding model for (TMTSF) 2 NO 3 where electron and hole pockets coexist [27][28][29] . In that system the dHvA oscillation has been usually studied in the phenomenological theory of magnetic breakdown 30,31 and the Lifshitz and Kosevich (LK) formula 32,33 . The dHvA oscillation and the LK formula [34][35][36][37] are explained in Appendix B.…”
Section: Introductionmentioning
confidence: 99%
“…The tunnel probability (10) evaluates for our model parameters to TðEÞ ¼ exp½−0.52NðE=tÞ 2 . The contribution of an orbit to the Fourier amplitude contains a factor t ¼ ffiffiffi ffi T p for each transmission through the Weyl point and a factor r ¼ ffiffiffiffiffiffiffiffiffiffiffi 1 − T p for each reflection [40]. In Fig.…”
Section: -2mentioning
confidence: 99%